TINDAK TUTUR ILOKUSI ASERTIF DALAM VIDEO LIVE DARI MANADO: CINTA UNTUK NEGERI PADA ACARA MATA NAJWA (KAJIAN PRAGMATIK) - Asti Feradila Parawita; Sainil Amral; Afif Rofii (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study is written to describe the use of assertive illocutionary act forms in the "Live dari Manado: Cinta Untuk Negeri" video aired on the Mata Najwa talk show. The type of research conducted is qualitative descriptive. The data in this study consist of utterances used in the forms of stating, informing, suggesting, and explaining in the Live from Manado: Cinta Untuk Negeri video on the Mata Najwa talk show. A total of 141 utterances were collected and analyzed using the theoretical framework outlined in the research indicator table. The most dominant type of utterance found in this video is the form of stating, with 59 utterances, while the least frequent form is suggesting, with only 10 utterances. Other forms include 54 utterances of informing and 18 utterances of explaining, all of which were found in the Live from Manado: Cinta Untuk Negeri video on the Mata Najwa talk show.